Shrub Expansion is Mainly Affected by Climate-Dominated Functional Traits in Alpine Meadow - Yang, Jianping; Su, Peixi; Zhou, Zijuan; Shi, Rui; Qin, Yanyan (Frontiers in Environmental Science, 2022)
Shrub expansion has been reported mostly in dry and semi-arid ecosystems worldwide. Shrub expansion is also a serious ecological issue in alpine and cold regions. Multiple drivers, including anthropogenic and environmental factors, contribute to this phenomenon. However, the relative effects of climate and soil factors on shrub expansion are incompletely quantified or understood in the alpine meadow, and quantifying how these factors result in variations in functional traits associated with shrub expansion is crucial considering that functional traits are tightly related to ecosystem processes. In this study, we investigated the vegetation of an alpine shrub meadow composed of Potentilla fruticosa L. in the Zoige Plateau, along an elevation gradient. We assessed the direct and indirect effects of climate and soil factors on functional traits, shrub expansion strength (measured as the total biomass), and relative abundance (via functional traits). We found that climate factors, namely, the mean temperature of the warmest quarter (bio10), mostly affected specific leaf areas and specific lobe volume, which were the most important traits related to shrub expansion. Soil factors, except soil water content (SWC), had weak effects on functional traits closely related to shrub expansion. Our partial least square path modeling model explained 99% of the variation in shrub biomass. Results suggest that climate change not only affected functional traits but also influenced shrub expansion in the Zoige Plateau. Thus, management measures to control expansion should consider these drivers for more accurate forecasting and cost effectiveness. Understanding the mechanism of alpine shrub expansion contributes to the delaying of the expansion process and ensures steady pastoral production.